Comparing two hydrazine addition strategies to stabilize mainstream deammonification: Performance and microbial community analysis. (October 2019) - Xiang, Tao; Gao, Dawen
Graphical abstract: Highlights: Variable N2 H4 concentration dosage make mainstream deammonification process stable. The inhibit effect of N2 H4 on AnAOB and AnAOB self-regulate mechanism was found. Variable N2 H4 concentration dosage was beneficial for most microorganisms. Abstract: In this study, an expanded granular sludge blanket reactor (EGSB) was proposed to achieve stable mainstream deammonification process by adding hydrazine (N2 H4 ). Two N2 H4 addition methods consisted of constant concentration (strategy A) and variable concentration (strategy B) both can inhibit nitrite oxidizing bacteria. A efficient performance was achieved with higher total nitrogen removal efficiency (82 ± 6%) and nitrogen removal rate (0.32 ± 0.02 kg N/(m 3 ·d)) under strategy B. For strategy A, anaerobic ammonia oxidizing bacteria (AnAOB) in-situ activity was decreased from 2.76 to 0.68 mg N/(g VSS·h) at 42 mg/L NH4 + -N. Candidatus Brocadia abundance increase from 14.62% to 20.07% under the strategy may indicated the self-regulate mechanism of AnAOB. Aerobic ammonia oxidizing bacteria (AOB, mainly Nitrosomonas ) and AnAOB (mainly Candidatus Brocadia ) were always dominated under two strategies. Strategy B provided better environment for most microorganisms (mainly Chloroflexri, Planctomycetes, Proteobacteria and Chlorobi ).